2008
DOI: 10.3892/mmr.1.4.599
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated expression of the per2 gene in human colorectal carcinoma

Abstract: Abstract. The circadian system is involved in the control of cell proliferation and apoptosis. The aim of this study was to analyze expression of the human per2 gene in patients who underwent surgery for colorectal carcinoma. The study included 25 patients of both genders. Patients were exposed to light from 6:00 a.m. until 9:00 p.m. according to standard hospital practice. Tissue samples were taken from the tumor as well as from the proximal and distal areas of the resected colon at the time of surgery. Surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…1). Characteristics of the 11 studies are given in Table 1 [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Characteristics of the 11 studies are given in Table 1 [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…One study found no difference [32]. Seven studies reported the gene expression of Per2 [27][28][29][30][31][32]36]: two showed a significant decrease [30,31] and five found no difference [27][28][29]32,36]. The gene expression of Per3 was examined in four studies, all of which found a significant decrease in gene expression [29,30,34,36].…”
Section: Gene Expression Of Period Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of 25 patients showed that colon and rectal tumor Per2 RNA levels correlated inversely with tumor stage, with Per2 levels declining with advancing stage. Compared with normal matched tissues, early-stage primary tumors (without or with nodal metastases) had increased Per2 levels, whereas primary tumors from advanced cancers (with distant metastases) had decreased Per2 levels compared with normal tissues [14]. Mostafaie et al [15] studied 30 patients and found decreased Per1 RNA levels in grade 2 and 3 (higher grade) CRCs in females, but only in grade 3 tumors in males, compared with normal tissues.…”
Section: Period Gene Mutations In Crcmentioning
confidence: 96%
“…A higher incidence of tumor development was observed in PER2-deficient mice than in wild-type mice [2]. In addition, clear differences in PER2 expression are evident in tumor tissue and non-involved peripheral tissues [3][4][5][6][7]. Elsewhere, overexpression and/or or mutations in the PER2 gene have been reported to correlate with enhanced tumor growth in breast cancer, colon cancer and lymphoma, corresponding with altered expression of TP53 and the oncogenes BCLxl, BCL-2, cyclinB1, cyclin D, cyclin E and C-MYC [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%